A modular approach to disease registry design: Successful adoption of an internet-based rare disease registry - Bellgard, M.; Macgregor, A.; Janon, F.; Harvey, A.; O'Leary, Peter; Hunter, A.; Dawkins, Hugh (Wiley Interscience, 2012)
There is a need to develop Internet-based rare disease registries to support health care stakeholders to deliver improved quality patient outcomes. Such systems should be architected to enable multiple-level access by a range of user groups within a region or across regional/country borders in a secure and private way. However, this functionality is currently not available in many existing systems. A new approach to the design of an Internet-based architecture for disease registries has been developed for patients with clinical and genetic data in geographical disparate locations. The system addresses issues of multiple-level access by key stakeholders, security and privacy. The system has been successfully adopted for specific rare diseases in Australia and is open source. The results of this work demonstrate that it is feasible to design an open source Internet-based disease registry system in a scalable and customizable fashion and designed to facilitate interoperability with other systems.